What’s the Point of Clinical Pastoral Education and Pastoral Counselling Education? Political, Developmental, and Professional Considerations - Lasair, Simon 1978- (2020)
Further clarity is needed regarding the uniqueness of spiritual care and psycho-spiritual therapy. In this article, this uniqueness is described as the relative spiritual health of spiritual health professionals. Drawing upon political philosophy, spiritual development theories, and studies in spiritual health, three traits of spiritual health are revealed that spiritual health professionals need to function effectively in their work environments. The article ends with four recommendations for both clinical pastoral education and pastoral counselling education.
Keywords: pastoral counselling education; Clinical Pastoral Education; Spiritual Health; psycho-spiritual therapy; Spiritual Care